2023
DOI: 10.3389/fpubh.2023.1136355
|View full text |Cite
|
Sign up to set email alerts
|

LTBI-negative close contacts of tuberculosis are more likely to develop the disease: enlightenment and lessons from a cluster outbreak

Abstract: BackgroundTuberculosis (TB) prevention and control among groups living together, such as students, workers, older adults in nursing homes, and prisoners, present many challenges due to their particular age and environmental factors, which can make them more susceptible to TB clusters with significant societal impact. This study aimed to evaluate a TB cluster outbreak epidemic in a university and provide suggestions for improving TB control strategies for groups living together.MethodsPulmonary TB screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The majority of infected individuals exhibit no symptoms and are classified as having LTBI. Without treatment, around 5−10% of LTBI patients will develop TB over their lifetime, emphasizing the importance of treating LTBI to prevent disease progression 9,150,151 . The Guidelines for the Treatment of Latent Tuberculosis Infection: Recommendations from the National Tuberculosis Controllers Association and CDC guide LTBI treatment.…”
Section: Therapeutic Intervention Strategies For Tbmentioning
confidence: 99%
“…The majority of infected individuals exhibit no symptoms and are classified as having LTBI. Without treatment, around 5−10% of LTBI patients will develop TB over their lifetime, emphasizing the importance of treating LTBI to prevent disease progression 9,150,151 . The Guidelines for the Treatment of Latent Tuberculosis Infection: Recommendations from the National Tuberculosis Controllers Association and CDC guide LTBI treatment.…”
Section: Therapeutic Intervention Strategies For Tbmentioning
confidence: 99%
“…Biomarker data is the most important source for using ML methods to diagnose LTBI [ 282 ]. Previous research has found significant differences between individuals with LTBI and individuals with ATB or healthy individuals in various biomarkers [ 13 , 67 , 283 , 284 ]. Biomarker data in latent TB diagnosis is obtained through biological experiments and includes information on molecules, cells, tissues, and fluids like blood, urine, sputum, and saliva.…”
Section: Future Directions Of ML For the Differential Diagnosis Of Ltbimentioning
confidence: 99%